Applying design thinking in public policy formulation and implications for Vietnam - Nguyen Ha Thi Quynh Trang; Pham Thi Tham; Pham Thi Linh (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2024)
Design Thinking first emerged as a concept around the 1950s - 1960s of the 20th century. However, the role and contributions of design thinking have been recognized not only in the field of design but also in the progress of science, business management, and education... In the field of public policy, design thinking is considered an approach that can be employed to tackle complex issues, offering tools for managers to explore creative opportunities, streamline organizations, and manage resources more effectively. In the policy-making stages, design thinking is regarded as an approach to better understanding and structuring the policy issues. It is characterized by a creative process involving multiple stakeholders, especially policy beneficiaries. Besides systematizing the basic concept of design thinking, this paper will summarize the potential of applying design thinking in the public policy cycle and discuss its debates and limitations, thereby offering suggestions for Vietnam. Code: 24102801